Synthesis and Properties of Dicephalic Cationic Surfactants Containing a Quaternary Ammonium and a Guanidine Group. Issue 1 (2nd November 2012) - Song, Yongbo; Li, Qiuxiao; Li, Yunling; Zhi, Lifei
Abstract: Novel dicephalic surfactants containing a quaternary ammonium and a guanidine group were synthesized, and the effect of the alkyl chain length on micellization and antimicrobial activity were investigated. Surface tension and conductivity were applied to study the self‐aggregation of the amphiphilic molecule in aqueous solution. The results indicated that these compounds reduce the surface tension to a level of 30–36 mN/m at the air/water interface and that there is a characteristic chain length dependence of the micellization process of surfactants. The antimicrobial activity was evaluated against Gram‐negative, Gram‐positive bacteria and fungi, indicating strong antibacterial activity against tested strains.